GOOGLE INSIGHTS FOR SEARCH FEATURES ANALYSIS - Moh. Muttaqin (Pusbindiklat - LIPI, 2012)
Google Insights for Search is a reliable application to know the search interests on Google search engine, furthermore this application usage can be developed to conduct the research of internet users searching behaviour. However, the limitations of tutorials that discuss this application’s features usage comprehensively resulted in some users unable to use it optimally. Google Insights for Search features analyzed by classifying the features group, list every feature, analyzed the variations of the value filled on these features and examined every link until the result page part to know its searching expandability. In this way, all the features functions and the optimal usage of Google Insights for Search will be explored.